Environmental tax and global income inequality: A method of moments quantile regression analysis - Osman Babamu Halidu; Amidu Mohammed; Coffie William (Cogent Business & Management, 2023)
Even though Environmental tax policy impacts inequality theoretically, empirical studies remain scanty not only in the context of volumes and the estimation approaches but are also focused on selected advanced countries, communities, households, and emerging countries, the neglect of the global or big picture effect, which is essential for measuring the overall effect of the collective and individual country-concerted efforts in addressing this global cancer. We provide empirical evidence in the global context using the novel method of moments quantile regression. We found that Income Inequality across the globe is sharply reduced by restrictive environmental tax policy, a finding that has ramifications for global sustainable development, particularly in dealing with the ravaging effects of Covid-19.
Keywords: 650; Climate Change; Environmental Tax; Global Inequality; Income level; Method of moments quantile regression